Examining The Effects of Silver Diamine Fluoride Treatment on The Surface Morphological Properties and Binding Strength of Demineralized Dentin to Glass Ionomer with and without Potassium Iodide and Glutathione - Samani, Mahsa; Hajebi, Farimah; Zakavi, Faramarz; Mapar, Mehran (Galen Medical Journal, 2024)
One new and promising chemical for non-invasive and minimally invasive dental caries treatment is silver diamine fluoride (SDF). However, demineralized dentin discolors easily, so it's not a popular choice for permanent teeth or the aesthetic zone. Although this discolouration can be reduced by applying glutathione and potassium iodide (KI) antioxidants, it is unclear how these substances affect the bond strength of glass ionomer (GI) to pre-treated dentin. Consequently, the objective of this research was to evaluate the degree to which dentin treated with SDF plus KI (SDF-KI), SDF plus glutathione (SDF-GLU), or a combination of the two (SDF+GLU) compared to GI in terms of microtensile bond strength (TBS). We artificially demineralized 75 dentin specimens taken from healthy human permanent teeth to mimic caries. After that, they were connected to self-cure GC-Fuji IX GI and treated in one of five groups: control, SDF, SDF-KI, SDF-GLU, or SDF+GLU (n=15). Their mode of failure was identified under a stereomicroscope after they went through a TBS test. Scanning electron microscopy (SEM) was also applied to a subset of specimens from both groups. The control and SDF-KI groups had significantly different TBS values (P=0.019 and P=0.005, respectively), as did the control and SDF-GLU groups. Compared to the SDF group, the SDF-KI group had a significantly lower TBS (P=0.024). There was a statistically significant difference between the SDF and SDF-GLU groups in terms of TBS (P=0.006). When comparing the control group to the SDF and SDF+GLU groups, there was no significant difference in TBS (P>0.05). For optimal dentin surface preparation prior to GI restoration, SDF+GLU is the way to go. The decrease in GI to dentin TBS is the reason why SDF-KI and SDF-GLU are not suggested.